Ethylene production processes in a carbon-neutral strategy - Jung, Wonho; Lee, Jinwon; Ha, Kyoung-Su (Energy conversion and management, 2024)
[Display omitted] •Global CO2 emission and economic evaluation for four different ethylene productions were conducted.•CO2 capture cost and carbon prices were applied to total CO2 emissions for CO2-based TEA of ethylene production.•Process electrification index for ethylene production was proposed and assessed.•DBD plasma-assisted ethylene production has the potential to significantly reduce CO2 emissions compared to existing ethylene production processes. Ethylene, a crucial chemical in the industry, has a 6.2 % annual growth rate, leading to a significant rise in demand. However, the substantial CO2 emissions from its production does not seem suitable any longer especially for “carbon–neutral” policy. In this regard, this study scrutinized the total CO2 emissions of existing ethylene production technologies (naphtha and ethane cracking centers) and emerging technologies such as methanol-to-olefin and dielectric-barrier-discharge plasma. A CO2-based TEA scenario for ethylene production was formulated based on the rigorous flow diagram of these four production technologies to analyze the economic feasibility predicated on CO2 emissions. Notably, the type of CO2 was discerned by labeling the CO2 emitted from the process, whereas the CO2 capture cost and carbon price were factored in for direct and indirect CO2 emissions, respectively. Furthermore, the introduction of renewable and alternative power generation technologies to the designed ethylene production technologies was discussed. To perform a fair evaluation under the constrained system, a comparison of the current commercial value of different ethylene production technologies with the future value, inclusive of CO2 emissions, was undertaken. Ultimately, when integrated with renewable energy, electricity-based ethylene production processes were found to be the most advantageous, with the highest potential to reduce CO2 emissions (∼90 %) compared to the conventional ethylene production technologies. This study provides a basis for active process electrification in the ethylene production industry and confirms the potential of the dielectric barrier discharge plasma reaction for ethylene production.